Pemberian Makanan Tambahan (PMT) Stik Modifikasi Berbasis Pangan Lokal Daun Kelor untuk Remaja Putri KEK - Masfufah Masfufah (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2022)
Nutritional problems are complex issues that require various techniques to address. Women of childbearing age, particularly malnourished adolescent girls, need attention because they influence the quality of future generations. Chronic Energy Deficiency (CED) in this group is a critical issue. This project aims to create moringa leaf-based supplementary food to increase iron intake for adolescent girls with CED in Daenggune Village, Central Sulawesi. The target is 20 adolescent girls. The methods include early detection of nutritional status through anthropometric measurements, education about CED, and organoleptic assessment of moringa leaf stick PMT based on taste, texture, aroma, and color. Success indicators for this activity are increased knowledge about nutritional status and understanding of nutritional problems and their management using local food such as moringa leaves. The results show that all participants attended the activity enthusiastically. The organoleptic assessment showed that 94% liked the taste and aroma of the moringa sticks, 89% liked the texture, and 78% liked the color. The evaluation also showed increased knowledge about nutritional status and the use of local food. In conclusion, this program effectively improves understanding of nutrition and the use of moringa leaves as an iron source. This activity is expected to continue with other local foods to address nutritional problems in adolescents.